Clinical Characteristics of Multiple Colorectal Adenoma Patients Without Germline APC or MYH Mutations. Issue 7 (August 2016) - Tieu, Alan H.; Edelstein, Daniel; Axilbund, Jennifer; Romans, Katharine E.; Brosens, Lodewijk A.; Wiley, Elizabeth; Hylind, Linda; Giardiello, Francis M.
Abstract : Background: Patients with multiple colorectal adenomas (MCRA) without genetic cause are increasingly being diagnosed. The characteristics and natural history of this condition are not well studied. Materials and Methods: Twenty-seven patients with MCRA, with cumulatively 10 to 99 colorectal adenomas and without deleterious mutations of APC or MYH genes, were investigated. Results of colonoscopies with a mean follow-up of 4.9 years (range, 0 to 27 y) were evaluated. Findings from esophagogastroduodenoscopy and extracolonic manifestations were assessed. Results: The mean age at polyp diagnosis and MCRA diagnosis was 47.8±13.1 years (range, 21 to 72 y) and 50.4±14.6 years (range, 21 to 72 y), respectively. In 22% of patients another family member had MCRA. At first colonoscopy, the mean number of adenomas was 35.0±35.9 (range, 0 to 99). Serrated polyps were rare. Esophagogastroduodenoscopy revealed 47% of patients had upper tract neoplasia. Patients with upper tract findings were diagnosed with MCRA at significantly younger mean age than those without findings, P <0.05. Eighteen patients (67%) underwent colectomy with a mean time from diagnosis of MCRA of 3.1±1.3 years. After surgery, surveyed patients developed recurrent adenomas in retained colorectum. Nine patients (33%) had extracolonic cancers. Conclusions: MCRA patients have a similar clinicopathologic phenotype to known syndromes of attenuated adenomatous polyposis and the majority have need for colectomy. The management of MCRA patients and families should parallel that of attenuated familial adenomatous polyposis and MUTYH -associated polyposis including surveillance of the upper tract.